Lived diversities : Space, place and identities in the multi-ethnic city - Husband, Charles (Policy Press, 2014)
Focusing on multi-ethnic interaction in an inner city area, this book addresses difficult issues that are often simplistically and negatively portrayed, challenging the stereotypical denigration of inner city life, and Muslim communities in particular.